Challenges of Contextualizing Low-Carbon Development in Indonesia - Romadhoni, Ahmad Ilham; Muta’ali, Lutfi; Paramitha, Dyah Pradjna; Tumus, Muhammad Galang Ramadhan Al (Amcolabora, 2025)
Climate change in Indonesia has triggered multidimensional disasters that are increasingly severe and difficult to predict, placing communities in vulnerable conditions. To address this, the Indonesian government has adopted the Low Carbon Development (LCD) paradigm, gradually integrating it into national and regional planning to pursue sustainable economic growth while minimizing carbon emissions. However, progress in low-carbon development remains limited. The gap is largely due to weak translation of LCD principles into sectoral programs, inadequate adaptive fiscal instruments, and poor alignment between regional development plans (RPJMD) and the LCD framework. This study aims to identify challenges from idea to plan to practice in the implementation of LCD policies in Indonesia and to propose a contextualized scheme for strengthening their application. Findings reveal three main challenges: (1) regional development orientation is still growth-centered rather than sustainability-oriented, (2) local governments have limited capacity to formulate and implement low-carbon programs, and (3) actor fragmentation and weak cross-sectoral and interregional coordination hinder integration. Furthermore, Indonesia’s vast geography presents structural and distributional constraints that demand creative, context-specific solutions rather than being accepted as fixed barriers. Overall, while Indonesia possesses substantial potential in low-carbon development, realizing it requires reorienting development priorities, enhancing local capacities, and improving institutional coordination. A contextualized LCD scheme must therefore address these systemic challenges to align national and regional development agendas with global commitments, particularly the net zero emission target.